A Critical Examination of Language Attitudes in the Novel Run and Hide by Pankaj Mishra - Abida Parveen; Dr. Durr-e-Nayab (Indus Journal of Social Sciences, 2025)
This research seeks to explore the intricate relationship between language attitudes and social inequalities in the context of the novel Run and Hide by Pankaj Mishra. Hence, the main objective is to reveal the way language in this particular novel seems to be as a symbol of power, class and identy within the boundaries of sociopolitical landscape of contemporary India to highlight the way a language can be shaped by social hierarchies. However, the second objective is to reveal how the narrative of this novel seems to critique social inequalities that a language can bring with. Fairclough (1989) approach of critical discourse has been employed as the framework of this study. Hence, the data has been analyzed under the lens of thematic analysis. The findings revealed an individual’s access to power and resources is often mediated by their linguistic proficiency, which can either facilitate or hinder their ability to succeed within a hierarchical social structure.